Fourier transform infrared spectroscopy for in-process inspection, counterfeit detection and quality control of anti-diabetic drugs. Issue 4 (2011) - Farouk Farouk, Faten Faten; Moussa Moussa, Bahia Abbas Bahia Abbas; Azzazy Azzazy, Hassan Mohamed El-Said Hassan Mohamed El-Said
Abstract : The purpose of this study is to develop simple and cost-effective Fourier transform infrared (FT-IR) methods for quality control evaluation of repaglinide (RPG), rosiglitazone maleate (RGZ), pioglitazone hydrochloride (PGZ) and metformin hydrochloride (MET) and assess their use for in-process quality control and detection of counterfeit medicine. The conventional KBr disc sampling technique used in FT-IR does not result in constant path-length thus impeding the use of this sensitive and simple technique for quantification of drugs. In this study, FT-IR quantitative assays were developed using a constant KBr disc pathlength to quantify drugs in bulk and tablets. Method validation was done according to the International Conference on Harmonization (ICH) guidelines and recovery studies were performed by applying standard addition technique. Samples representing pitfalls at different tablet manufacturing stages and counterfeit medicines were prepared and tested by FT-IR. The developed methods achieved ICH validation parameters. Statistical comparison of the results with reference or reported methods showed no significant difference with respect to method accuracy and precision. The methods were applicable to tablet dosage form with average recovery ranging between 99 and 102%. The developed methods are capable of detecting impurities that result from in-process manufacturing problems and counterfeit products and are inclusive for in-process and end product testing.